Relationship between real exchange rate and consumption in Nigeria: A nonlinear approach - Jamilu S. Babangida; Aliyu R. Sanusi; Isah M. Yusuf (CBN Journal of Applied Statistics, 2021)
This study analyses the relationship between real exchange rate and domestic con- sumption in Nigeria using the Smooth Transition Autoregressive (STAR) model from 1981Q1 to 2019Q4. Findings show that domestic consumption determines the regime shift in real exchange rate, suggesting a nonlinear linkage with clearly distinct regimes. The lagged exchange rate is shown to have a significant linear effect on the current exchange rate. On the other hand, current foreign consumption is positive but has no significant impact on the exchange rate in the linear part of the model. In the nonlinear part of the model, evidence of a significant negative relationship between real exchange rate and domestic consumption is found, thus, supporting the propo- sition of the standard international business cycle model. In addition, the study finds evidence of bi-directional nonlinear granger causality between real exchange rate and domestic consumption. The study concludes that the relationship between real exchange rate and domestic consumption is nonlinear and that fiscal and monetary authorities should aim at policies that would stimulate domestic consumption below the threshold level necessary to keep the exchange rate stable
Keywords: F31; F44; 330; international real business cycle; nonlinear; real consumption; real ex-change rate; smooth transition autoregressive model